Theoretical and phenomenological study for the production of heavy neutrinos and majorons at the LHC (2020)
"The Following monograph presents an extension of the Standard Model, known as the minimal singlet majoron model, with the difference that this work assumes a massive majoron in contrast with other models. This model proposes the existence of heavy right-handed neutrinos and a pseudo-Goldstone particle called majoron. This extension shows that the so-called Type 1 See-Saw mechanism could be explained as a consequence of the (B - L) number violation. The corresponding symmetric gauge-invariant Lagrangian is derived for this model. The main contribution of this monograph is the implementation of the massive majoron model using the FeynRules package within the Mathematica framework, to produce the so called Universal FeynRules Output (UFO). The UFO is used as input for the MadGraph program in order to emulate the hypothetical production of the associated particles in the model at the LHC. Preliminary phenomenological studies are presented, considering the production of heavy neutrinos and majorons through a W-channel process qq ? l? l+ l? J ?l"--Tomado del Formato de Documento de Grado